Reconstruction of Legal Policy on Online Gambling within the Indonesian Legal System: Perspectives of ITE Law and Islamic Criminal Law - Ulya Shafa Firdausi; Dian Rosita; Salma Amellia (CV. Era Digital Nusantara, 2025)
This study aims to examine in depth the phenomenon of increasing online gambling practices in Indonesia from the perspective of positive law and Islamic criminal law. The focus of the study is directed at the legal basis of prohibition, the similarity of principles, and the efforts of the two legal systems in tackling these crimes. This study uses a normative legal approach by analyzing various relevant legal provisions, especially Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE) and its amendments, as well as the principles of Islamic criminal law related to jarimah ta'zir. The novelty of this study lies in its integrative normative analysis that reconstructs legal policy by harmonizing positive law and Islamic criminal law, thereby contributing theoretically to the development of legal policy studies on online gambling in Indonesia. The study's findings show that Article 27, paragraph (2), of the ITE Law serves as the legal basis for prohibiting and sanctioning the dissemination of content containing gambling elements through electronic media. On the other hand, Islamic law expressly prohibits any form of gambling because it is considered to bring more harm than benefit. It can be concluded that both positive law and Islamic law have a harmony of views in viewing online gambling as a destructive act and have the potential to hurt morality, social order, and the economy of society, so both emphasize the importance of prevention and enforcement of the practice.